Real Life Application of Consumer and Producer Surplus - khatun, Aafrin; Sah, Sarswati Kumari; Sahani, Suresh Kumar; Mahto, Shyam Kishor (Darul Yasin Al Sys, 2024)
In this assignment, we addressed the usage of consumer and producer surplus in various sectors as business sector, medical sector, engineering sector, non profit sector and educational sector. Businesses employ consumer excess to draw in new clients, boost client satisfaction, expand their product offerings, and maintain their position as leaders in their sector. The idea is to determine what advantages consumers can have from purchasing a product and then reduce the price of that product to provide those advantages to them in excess.